2008
DOI: 10.1029/2008eo300001
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Tomography Experiment at Italy's Stromboli Volcano

Abstract: Stromboli Island, located in the southern Tyrrhenian Sea, is the emerged part (about 900 meters above sea level) of an approximately 3‐kilometer‐high stratovolcano. Its persistent Strombolian activity, documented for more than 2000 years, is sometimes interrupted by lava effusions or major explosions. Despite the number of recently published geophysical studies aimed at clarifying the volcano's eruption dynamics, the spatial extent and geometrical characteristics of its plumbing system remain poorly understood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 8 publications
(5 reference statements)
0
21
0
Order By: Relevance
“…Recently, a P wave image of Stromboli Volcano in Southern Italy has been achieved with active data [ Castellano et al , ; Patané et al, in preparation, 2015]. We propose in the present work a complementary attenuation image of the same zone, achieved using the same active data set.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Recently, a P wave image of Stromboli Volcano in Southern Italy has been achieved with active data [ Castellano et al , ; Patané et al, in preparation, 2015]. We propose in the present work a complementary attenuation image of the same zone, achieved using the same active data set.…”
Section: Introductionmentioning
confidence: 95%
“…Then, Q i and Q s were calculated from equations and . In this estimation we assume p = 3 and v = 2.8 km/s derived from Castellano et al [] and considering the predominance of S waves in our seismograms as indicated by Yamamoto and Sato []. As the final step, we estimated the transport mean free path, l tr , and the absorption length, l i coefficients using the expressions l tr =3 d / v and l i = v / b , where d is the average diffusivity and b the average intrinsic‐attenuation coefficients obtained above.…”
Section: Data Processing and Mapping Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…In the frame of an INGV‐Italian Civil Defense project, part of which is aimed at better understanding the internal structure of the volcano and locating magma reservoirs, the first seismic tomography experiment was undertaken at Stromboli toward the end of 2006 [ Castellano et al ., ]. This in order to (i) better comprehend its activity, (ii) help predict the next eruption scenario, (iii) interpret the pattern of the expected precursory seismic activity and ground deformation field induced by magma upraise mechanisms in the shallow storage zones and along the feeding conduits, and (iv) better model edifice stability and associated hazards.…”
Section: Introductionmentioning
confidence: 99%